Emission Characteristics of a Diesel Engine Fueled by 25% Sunflower Oil Methyl Ester and 75% Diesel Fuel Blend - Ilkilic, C. (Taylor & Francis Inc, 2009)
Combustion of fossil fuels is the main culprit in increasing the global carbondioxide level, a consequence of global warming. Diesel engines are the major source of greenhouse gas emissions (CO2) and other air pollutants, such as HC, CO, NOx, and smoke. One way of reducing these emissions or air pollutants is by the utilization of renewable alternative fuels for diesel engines, like vegetable oils. High viscosity is one of the major problems relating to the direct use of vegetable oils as diesel fuels. One method of reducing viscosity is by blending with a low viscosity and volatile fuel. This article investigates the emission characteristics of the fuel blend of 25% sunflower oil methyl ester with 75% diesel fuel (25/75 fuel) in a single cylinder unmodified diesel engine. The results show that 25/75 fuel has better emission characteristics than diesel fuel.
Keywords: diesel engine; diesel fuel; exhaust emissions; 25; 75 fuel